(untitled) (Journal of Engineering Science, 2021)
Experimental investigation requires materials, radiation sources, and test arrangements with a high monetary financial plan. Furthermore, radiation exposure involves people during the experiment. On the contrary, the simulation technique for examining radiation interactions is radio-logically safer, less timeconsuming, cost-effective, and applicable for all desired radiation sources. Through 48.86 mCi 662 keV Caesium-137 gamma-ray source; shielding experiment as well as simulation of it with MCNPX were performed for three shielding materials Lead, Copper, and Aluminum. These materials were placed in front of the gamma source and the emergent radiation was counted in a Geiger- Muller detector to understand the attenuation quality of these materials to each other. These courses of action were simulated utilizing the MCNPX code version 2.7.0 and the results likewise gave and looked at that of the experiment. There are huge similarities of shielding behavior between MCNPX simulation and experiments for the three absorbing materials. The modeled geometry of this MCNPX simulation could be used for future approaches of new designs and structures of radiation shielding, especially where no analogous experimental data exist Journal of Engineering Science 12(2), 2021, 11-21